1986
DOI: 10.1017/s0043174500026448
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Senna (Cassia occidentalis) Competition with Cotton (Gossypium hirsutum)

Abstract: Field research was conducted at two locations in 1982 and 1983 to evaluate the competitiveness of coffee senna (Cassia occidentalisL. # CASOC) with cotton (Gossypium hirsutumL.). With season-long competition, each increase of 1 coffee senna plant/7.5 m of row reduced seed cotton by 9 to 117 kg/ha. Each additional week of competition from a dense stand (40 plants/m of row) of coffee senna reduced seed cotton yield by 118 kg/ha and cotton main stem height by 1.25 cm. Neither cotton stand density nor fiber proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
2
12
1
Order By: Relevance
“…Being allelopathic, it inhibits the germination and growth of other plants. Studies have shown that it has a negative impact on maize (Arora, 2013) and cotton yields (Higgins et al, 1986) and is an alternative host for crop diseases (Suteri et al, 1979). The seeds of S. occidentalis are highly toxic, containing compounds that damage the liver, the vascular system and the heart and lungs of domestic livestock, often leading to death in cattle (Barros et al, 1999), horses (Riet-Correa et al, 1998), goats (Suliman et al, 1982;Suliman and Shommein, 1986), pigs (Martins et al, 1986), poultry (Haraguchi et al, 1998), and rabbits (O'Hara and Pierce, 1974).…”
Section: Impactsmentioning
confidence: 99%
“…Being allelopathic, it inhibits the germination and growth of other plants. Studies have shown that it has a negative impact on maize (Arora, 2013) and cotton yields (Higgins et al, 1986) and is an alternative host for crop diseases (Suteri et al, 1979). The seeds of S. occidentalis are highly toxic, containing compounds that damage the liver, the vascular system and the heart and lungs of domestic livestock, often leading to death in cattle (Barros et al, 1999), horses (Riet-Correa et al, 1998), goats (Suliman et al, 1982;Suliman and Shommein, 1986), pigs (Martins et al, 1986), poultry (Haraguchi et al, 1998), and rabbits (O'Hara and Pierce, 1974).…”
Section: Impactsmentioning
confidence: 99%
“…population and cotton [Gossypium hirsutum (L.)] yield (17), cotton yield showed a four-fold difference in the effect of each addi tional coffee senna plant between the 2 yr at one location, more than a sixfold difference between years at the same location, and a two-to three -«0 fold difference between the two locations in the same year. Similarly, the relationship between velvetleaf (Abutilon theophrasti Medik.…”
Section: Casoc)mentioning
confidence: 99%
“…Tall morningglory [I. purpurea (L.) Roth], entireleaf morningglory (I. he{Jeracea var. illtegriuscula Gray), ivyleaf morningglory, and pitted morningglory (I. lacullosa L.) densities of 8 weeds/IS m of row reduced cotton yield 19,9,6, and 30/0, respectively. At densities of 32 weeds/IS ill, those species reduced yield 88, 50,44, and 44%, respectively.…”
Section: Introductionmentioning
confidence: 99%